2019
DOI: 10.1186/s13065-019-0590-y
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable process for the recovery of volatile constituents from Gracilaria lemaneiformis in agar production and evaluation of their antioxidant activities

Abstract: Background Gracilaria lemaneiformis is a common red alga used as a raw material source for the agar industry. Its extract is rich in natural volatile constituents (VCs) having antioxidant activities. Herein, a sustainable method was used to recover VCs from the alga. The chemical composition of VCs present in the n -hexane fraction was analyzed by gas chromatography–mass spectroscopy (GC–MS) and the antioxidant potential was measured using a series of in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Polysaccharide derived sulfated and acetylated derivatives from G. lemaniformis are strong antioxidants observed by Wang and the group [74]. Volatile constituents of G. lemaniformis also possesses antioxidant activities since in vitro biochemical assays such as hydroxyl radical, DPPH and superoxide radical scavenging assays performed by Yuan et al [75] demonstrated this evidence. G. lemaniformis extract derived antioxidant activities through SOD, CAT and POD mediated was also reported by many other groups [76].…”
Section: Pharmacological Prospectsmentioning
confidence: 81%
“…Polysaccharide derived sulfated and acetylated derivatives from G. lemaniformis are strong antioxidants observed by Wang and the group [74]. Volatile constituents of G. lemaniformis also possesses antioxidant activities since in vitro biochemical assays such as hydroxyl radical, DPPH and superoxide radical scavenging assays performed by Yuan et al [75] demonstrated this evidence. G. lemaniformis extract derived antioxidant activities through SOD, CAT and POD mediated was also reported by many other groups [76].…”
Section: Pharmacological Prospectsmentioning
confidence: 81%
“…Yuan et al [69] performed the depigmentation of G. lemaneiformis by 3-times extraction with 70% ethanol (50:1, v/w) for 30 min each time. The dried Gracilaria debilis was ground and extracted with a mixed solvent of acetone/chloroform/methanol (2:1:1; v/v/v) in a Soxhlet apparatus for 48 h to produce depigmented seaweed [24].…”
Section: Depigmentationmentioning
confidence: 99%
“…21 More importantly, antioxidant compounds can protect human health and food safety from reactive oxygen species (ROS) oxidizing reactions. 22 Res is a natural compound in different plants, including peanuts, grapes, pines, and berries. 23 Moreover, Res is a natural plant antitoxin with antioxidant properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a source of antioxidants, plants can be used in the food industry to protect against lipid rancidity and oxidation and maintain food quality . More importantly, antioxidant compounds can protect human health and food safety from reactive oxygen species (ROS) oxidizing reactions . Res is a natural compound in different plants, including peanuts, grapes, pines, and berries .…”
Section: Introductionmentioning
confidence: 99%